O uso da experimentação no ensino da eletricidade e magnetismo no 9º ano do ensino fundamental - Neri, Mateus Oliveira (Brasil, 2023)
This is a proposal for the use of experimentation to teach electricity and magnetism in the 9th grade of Elementary School, which was carried out together with the Supervised Internship at the José Roberto Tadros Education Center - SESC in two 9th grade classes, with a quantity total of 70 students. The general objective of this work is to demonstrate that the use of experimentation can provide meaningful learning, and the specific objectives are: to investigate through observation, relevant characteristics of students for organization and planning of conducting; identify students' prior knowledge; use experiments to teach electricity and magnetism; and relate theoretical knowledge to experimental knowledge. This work is divided into four moments: observation, conducting, experimentation and data collection. This is based on the Theory of Meaningful Learning, proposed by David Ausubel in which a previous knowledge is related to a new knowledge, giving rise to a new knowledge present in the student's cognitive structure. During the project, two activities are proposed to students, one at the end of observation and the other at the end of experimentation. Thus, when analyzing the results obtained through the responses, it was found that learning, in fact, was significant.